Structural failure process of schistosity rock under microwave radiation at high temperatures (Fracture and Structural Integrity, 2019)
The effects of high temperature induced by microwave radiation on the schistosity structural rock were investigated. A 1.45 kW commercial microwave system was employed to irradiate specimens to a designed temperature (300–800 °C) for 15 minutes. Cracking and local melting initially appeared in the biotite enrichment area at 500 °C. Macro-cracks in the dark area were parallel to the schistosity trend, owing to the weak connection in a direction perpendicular to the schistosity plane. The composition of the rock did not significantly change before and after microwave radiation. The diffraction peak intensity of the biotite decreased with temperature increase, owing to melting. The average peak stress decreased significantly with increasing temperature. It is concluded that the high temperature induced by microwave radiation promotes hard rock breakage and the schistosity structure of rock significantly affects the cracking pattern.
Keywords: Microwave radiation; Schistose granite; High temperature; Thermal damage